2017
DOI: 10.1016/j.jtcvs.2017.03.119
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive outcomes and health-related quality of life in adults two decades after the arterial switch operation for transposition of the great arteries

Abstract: Despite satisfactory outcomes in most adults with transposition of the great arteries, a substantial proportion has cognitive or psychologic difficulties that may reduce their academic success and quality of life. Further studies are needed to better understand the long-term outcome of this population to provide prevention, surveillance, and care strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
(29 reference statements)
0
11
0
Order By: Relevance
“… No statistically significant difference in the mean SF6D scores between ASO patients and the general Australian population (18–24 age group: [0.769 for ASO patients vs 0.772 for Australian population, P = 0.85]; 25–34 age group [0.795 for ASO patients vs 0.780 for Australian population, P = 0.33]). Kalfa et al [ 33 ]: Evaluated the cognitive and psychological outcomes of 67 ASO adults (18.0–31.0 years) compared to 43 matched controls using the Short Form 36 (SF-36). ASO patients had a statistically significant lower physical component summary compared to controls (52.1 ± 7.5 vs 55.4 ± 5.9, P = 0.01).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… No statistically significant difference in the mean SF6D scores between ASO patients and the general Australian population (18–24 age group: [0.769 for ASO patients vs 0.772 for Australian population, P = 0.85]; 25–34 age group [0.795 for ASO patients vs 0.780 for Australian population, P = 0.33]). Kalfa et al [ 33 ]: Evaluated the cognitive and psychological outcomes of 67 ASO adults (18.0–31.0 years) compared to 43 matched controls using the Short Form 36 (SF-36). ASO patients had a statistically significant lower physical component summary compared to controls (52.1 ± 7.5 vs 55.4 ± 5.9, P = 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies evaluated the quality of life of ASO survivors [32][33][34][35][36][37][38]. They used different scales and reported on different aspects, hence a meta-analysis of the results was not possible, and the results were narratively summarised (see Table 2).…”
Section: Quality Of Life Outcomesmentioning
confidence: 99%
“…The lifetime prevalence for anxiety and depressive disorders was 54 and 43%, respectively, reflecting a highly significant increase compared with the control group. In contrast, the same group reported no increase of depression or anxiety in adult patients with TGA after ASO if the current and not the life-time prevalence was evaluated for example using the HADS questionnaire ( 25 , 26 ). These findings underline the need for repetitive testing for psychiatric distress in adults with congenital heart disease.…”
Section: Discussionmentioning
confidence: 93%
“…Our results suggested that quality of life in ASO survivors is similar to that of the general population. Likewise, this topic was recently addressed by Kalfa and colleagues [37], who investigated cognitive and quality-of-life outcomes in 67 adult ASO survivors 18 to 31 years of age. In their study, despite patients reporting an overall satisfying quality of life, cognitive difficulties and impairments occurred in 31% of survivors compared with 16% in the general population.…”
Section: Long-term Cognitive Outcomes and Quality Of Life After Asomentioning
confidence: 98%